Survey and characterization of corbelled dome architecture in Northwestern Portugal - Barroso, Carlos E. (2016)
The act of overlaying stones to build masonry structures is one of mankind’s most intuitive and resourceful achievements. Masonry buildings can be found all over the world, built with a wide diversity of materials and serving for all kind of purposes. In rural northwestern Portugal, in a granitic highland landscape of scarce resources, for centuries, local farmers used masonry in order to make the territory suitable for farming. In their effort to increase production and, by doing so, to improve their living conditions, a specific mountain agro-pastoral system was developed. Supported by communitarian labour, this system was based on terrace farming and temporary mountain plateau settlements, called brandas, composed of granite corbelled dome buildings. In spite of its perfect adaptation to the harsh local conditions, this heritage’s morphological and typological diversity and constructive inventiveness is endangered due to decades of rural exodus and, thus requiring urgent study and protection. The research project aims to study this heritage from morphological, typological and constructive points of view, with the objective of proposing guidelines towards its preservation. To achieve the established goals, a four stage based methodology was established. Literature review and fieldwork surveys were performed in the first stage, in order to identify possible case studies. On the second stage, an exhaustive geometrical survey and a case study analysis were undertaken and complemented with the local granite’s physical and mechanical characterization. The third stage aims to do an overall structural safety evaluation of the corbelled domes, based on numerical analysis. In the final stage, consolidation and preservation guidelines to safeguard this architectural heritage will be proposed. This paper presents the results of the first stage, along with a glimpse of the second stage.